Analyzing knowledge, attitude and practices on HIV/AIDS among female sex workers - Hlaing, Thu Thu Nwe (KDI School, 2011)
HIV/AIDS, being regarded as a disease of modernity (Schoepf, 2001) and a disease of globalization (Barnett & Whiteside, 2002), is a major threat to the development of humankind all over the world. Myanmar ranks third among five most HIV/AIDS burdened countries in South East Asia. As the result, effective HIV prevention methods are necessary in the country, and successful prevention method depends on changing risk behaviors. Although limited studies were done on female sex workers (FSW), one of the most-at-risk population groups, to measure the HIV prevalence among this population, the question of the relation between knowledge and practices of FSW remains unanswered. This study endeavors to fill that gap by comprehensively analyzing the relationship between knowledge of FSW on HIV/AIDS and their risk behaviors as well as several other factors preventing them from safe sex practices. It was found out that regardless of the high knowledge of HIV transmission methods, lack of condom use within the bonds of marriage and relationships between female sex workers and their regular partners in Myanmar is exposing both male and female partners to HIV and STD risk. Therefore, it is recommended to strengthen the knowledge of condom use among the population of young girls with no education on HIV/AIDS since they are more likely to practice unsafe sex at their first sexual experience and this would lead to less safe sex practices when they grow old.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: HIV/AIDS.